A qualitative exploration of nonconsensual pornography sharing experiences and influences among adult males - Webb, Brandy Lea (Kansas State University, 2021)
This study explores nonconsensual pornography sharing experiences and influences among older-generational males to answer the following research questions: What does the sharing of nonconsensual pornography look like among older-generational male peer groups? What influences men to engage in NCP sharing? Interviews were conducted among a sample of 18 adult males, 35 years and older, who have engaged in nonconsensual pornography sharing behaviors within the past 5 years. Participants were asked questions about their technology use, nonconsensual pornography sharing methods, and what influences might be associated with their NCP sharing behaviors. Qualitative analysis indicates that among adult men, nonconsensual pornography sharing is commonly facilitated through technology, and sharing behaviors are influenced by patriarchal standards of society, the need to perform masculinity, and engage in male bonding. Following this analysis, it is recommended that further research be conducted to differentiate between nonconsensual pornography behaviors motivated by nonharmful and harmful intent.
Keywords: Nonconsensual pornography; NCP; Image-based sexual abuse; Male peer support